Solubility of Drug Olopatadine Mouth Dissolving Film - Varsha, Ahirwar (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: This study was to perform their solubility of drug olopatadine oral film to evaluate their solubility mouth dissolving film in different solvent and artificial saliva and drug olopatadine hydrochloride solubility in different solvent. Materials and Methods: The olopatadine hydrochloride film was prepared by solvent casting method that is used for prepared oral strip solubility study in ex vivo method for avoid animal testing this study easy to help for solubility testing of film in saliva dissolution time solubility of drug to check in ultravioletspectrophotometric method. Results: The prepared oral strip showed satisfactory results for the evaluation parameters oral strip as optimized batch was evaluated. Conclusion: Overall this study indicated the enhancing the solubility of a poorly water soluble drug and this film formulation is easily solubilized the drug and its bioavailability is increased. Solubility of drug in different solvent is study in this formulation.